Governmentality and neoliberalism: a study of media discourse on poverty in Hong Kong. (1st February 2020) - Lo, Wai Han
Abstract : This study uses a governmentality approach to examine poverty and welfare media discourse as a complex aggregate of a wide variety of knowledge and political rationalities aimed at governing citizens. A discourse analysis of newspaper articles about poverty from 1994 to 2013 was conducted. Five discursive strategies and four oppositional claims were found in the 20-year sample period. The findings illustrate the relationship between neoliberalism and governmental strategies in poverty discourse.